The Effectiveness of Technology-Based Instructional Media in Enhancing Students’ Understanding of Chemistry Concepts; A Literature Review - Ardhelia Zahra Putri; Nabillah Amanda; Mutiara Elsa Nadila; Riska Amalia; Silvya Isra; Abdullah (Chatra: Jurnal Pendidikan dan Pengajaran, 2025)
Chemistry learning is often perceived as challenging due to the abstract nature of many of its core concepts, which are not directly observable. This condition leads to limited conceptual understanding and low student engagement during instruction. This study aims to examine the effectiveness of technology-based instructional media in enhancing students’ understanding of chemistry concepts and to identify the specific pedagogical contributions of different technological media. A qualitative literature review was employed using systematic content analysis of relevant scientific articles. Data were categorized according to media type, instructional use, and impact on cognitive processes and learning outcomes. The results reveal that technology-based media including educational videos, interactive simulations, virtual laboratories, mobile applications, and interactive e-books significantly improve students’ conceptual understanding of chemistry. Each medium offers distinct pedagogical benefits, ranging from fostering visualization of abstract phenomena to strengthening experimental skills and promoting learner autonomy. The study concludes that the selection of instructional media must align with the characteristics of the content, learning objectives, and student profiles to achieve optimal effectiveness. These findings contribute to the advancement of technology-integrated chemistry education and provide a foundation for future empirical research to evaluate media effectiveness more comprehensively.